An Optical Fibre Telephone System (System Analysis) (Part B) - Jurenas, Algis K. (My University, 1981)
No abstract was provided.
One of two project reports. Part A can be found at: http://hdl.handle.net/11375/18452
Keywords: engineering physics; optical fibre; telephone system; system analysis